A Study of the On-going Processes of Pre-service Elementary Teacher Education Programme in Maharashtra - Bawane, Jyoti (INDIAN EDUCATIONAL REVIEW, 2013)
‘The destiny of India is being shaped in its classroom’ as quoted by Kothari Commission has its relevance even today to re-emphasise that Education is one of the factors that contributes significantly towards nation’s building and development. It is certainly true that the progress of our country to a large extent depends on its quality of education imparted in schools and higher education institutions. The strength of an education system, on the other hand, largely relies on the quality of teachers, who play a vital role in imparting this‘quality education’ within the classrooms. However, the performance of teachers is likely to depend on the kind and nature training they had received during the pre-service programme. This ultimately lead us to the core factor, the teacher education programmes which are accountable for developing competent teachers who are expected to perform effectively in different educational systems. This in other words, implies that the school education has a symbiotic relationship with the teacher education